Epigenetic aberrant methylation of tumor suppressor genes in small cell lung cancer - Wang, Shuai (Pioneer Bioscience Publishing Company, 2013)
Small cell lung cancer (SCLC), a special type of lung cancer, is reputed to carry a poor prognosis. The morbidity of SCLC is increasing in China and other countries. A variety of DNA alterations associated with non-small cell lung cancer (NSCLC) have been described. However, genetic and epigenetic changes of SCLC are not well established. Few studies have demonstrated that epigenetic silencing of key tumor suppressor genes (TSGs) is pivotal to initiation and development of SCLC. Recently, promoter methylation of many TSGs have been identified in SCLC. These novel TSGs are potential tumor biomarkers for early diagnosis and prognostic prediction. Moreover, epigenetic promoter methylation of TSGs could be a target of intervention with a wide prospect of clinical application. This review summarizes recent studies on promoter methylation of TSGs in SCLC and aims to provide better understanding of the promoter methylation in tumorigenesis and progression of SCLC.